EDUKASI DINI TERHADAP BAHAYA MEROKOK DAN PENYALAHGUNAAN GANJA PADA ANAK-ANAK DI GAMPONG IE SEUUM KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Samsuar, Samsuar; Muzana, Syarifah Rahmiza; Hasanah, Hasanah; Winarty, Asih; Maslida, Maslida (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
The number of child smokers currently continues to increase. So prevention must be carried out by providing education from an early age. The purpose of this service is to provide education to gain knowledge for the children of Ie Seuum Village, Mesjid Raya District, Aceh Besar Regency, Aceh Province regarding the dangers of smoking and marijuana abuse. The method used is lectures and discussions using PowerPoint slides. The activities carried out include children in Ie Seuum Village gaining knowledge about the dangers of smoking and marijuana abuse including various types of cigarettes and marijuana, the dangerous chemical content of cigarettes and marijuana, chronic diseases caused by smoking and marijuana abuse, and the risk of disability. life and death, and the basis of state and religious laws regarding cigarettes and marijuana. Children responded well to educational activities, understood the material presented, were interested in the pictures displayed, asked questions about the dangers of smoking and marijuana and answered questions from educational presenters.